Prevalence of aggression and associated factors among inpatients with mental illness at tertiary hospitals in Southwestern Uganda - Badru Kayongo; Godfrey Zari Rukundo; Alain Favina; Samuel Maling (BMC Psychiatry)
Abstract Background In mental health treatment facilities around the world, aggression aimed towards medical personnel and other patients is a serious issue. Types of aggression include; verbal aggression, aggression towards property, self-harm/auto-aggression, and physical aggression. Studies show 1 in 5 patients admitted to acute mental health care wards in high-income countries commit an act of physical violence during admission. In Uganda, there is limited literature on aggression among patients with mental illness admitted in psychiatric wards in our setting. This study aimed to investigate prevalence, types and associated factors of aggression among patients with mental illness admitted at tertiary hospitals in southwestern Uganda. Methods This was a cross-sectional study that involved 280 participants from four tertiary hospitals in southwestern Uganda. Aggression was assessed using the Modified Overt Aggression Scale. The sociodemographic and clinical characteristics were collected using a structured sociodemographic questionnaire. The prevalence of aggression was assessed using proportions and the associated factors were assessed using the multinomial logistic regression analysis. Results The prevalence of severe aggression was 42.9% with verbal aggression being the most common type while auto aggression was the least common. Involuntary admission and having a personal history of aggression were associated with all the 3 levels of aggression: mild, moderate and severe aggression, while having a positive family history of mental illness was associated with two levels of aggression (moderate and severe aggression). Having a history of substance use was only associated with moderate aggression and having history of childhood abuse was associated with severe aggression. Coming from a rural area was associated with severe aggression. Conclusion The prevalence of aggression is high among patients with mental illness admitted at tertiary hospitals in southwestern Uganda with verbal aggression being the commonest. Mental health professionals should pay attention to aggression among patients bearing in mind that people admitted involuntary, with personal history of aggression have a high likelihood of presenting with aggression. The mental health treatment facilities should consider adopting more of voluntary admission for patients presenting with aggression and only utilize involuntary admission when it is absolutely necessary and in line with the rights and responsibilities for patients with mental illness.